The Nation as “International Bastard”:: Ethnicity and Language in Michael Ondaatje’s The English Patient - Smyrl, Shannon (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2003)
The characters of the English patient and Kip in Michael Ondaatje's The English Patient each employ different strategies of identity relating to nation and empire. These mirror the opposing strategies for criticism of Canadian literature. Robert Kroetsch "argues for a resistance to privileged metanarratives," but with a kind of homogenization of ethnic experience; Alison Conway and Linda Hutcheon argue against this homogenization, insisting that ethnic difference is crucial, and that "a double construction of ethnicity as social condition and as literary category…define[s] a coherent national literature." Ondaatje's novel—unlike the movie based upon it—privileges the idea of difference, interrogating the inclusive Romance of the English patient's love story as itself a metanarrative generated from imperial authority.